Beta-blockers reduced the risk of cardiac rupture in patients with acute myocardial infarction: A meta-analysis of randomized control trials. (1st April 2017) - Gong, Wei; Feng, Siting; Wang, Xiao; Fan, Jingyao; Li, Aobo; Nie, Shao-ping
Abstract: Background: Cardiac rupture (CR) is a catastrophic complication that occurs after acute myocardial infarction (MI) and, at present, there are no effective pharmacological strategies for preventing this condition. The objective of this meta-analysis was to assess the effect of beta-blockers on CR in patients with acute MI. Methods: An extensive search of the PUBMED, EMBASE, ISI Web of Science, MEDLINE and Cochrane was performed to retrieve the studies of beta-blockers treatment in patients with acute MI. Data were combined using a random effects model. A meta-analysis was performed using Review Manager 5.3. Results: Four randomized controlled trials (RCTs) involving 68, 842 patients, 603 of whom occurred CR, were met criteria. Meta analysis showed that beta-blockers caused a statistically and clinically significant decrease in the incidence of CR of 32% ( RR: 0.68, 95% CI: 0.47 to 0.99, P  = 0.04). Conclusions: The findings of this meta-analysis confirmed that the early use of beta-blockers is associated with decreased incidence of CR, suggesting some beneficial effects of beta-blockers on infarct healing after acute MI.